PENGARUG PENDEKATAN PEMBELAJARAN STEM TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATA PELAJARAN IPAS SDN 70 BODDIA - Kinarun, Arvina; Ma’ruf; Amri Amal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Arvina, 2026. The Effect of the STEM Learning Approach on Problem-SolvingAbility in Science and Social Studies (IPAS) for Fifth Grade Students at SDN 70Boddia. Undergraduate Thesis, Department of Elementary School TeacherEducation, Faculty of Teacher Training and Education, Universitas MuhammadiyahMakassar. Supervisor I: Ma’ruf and Supervisor II: Amri Ama This research wasmotivated by problem-solving abilities in the learning process. One alternativelearning model that can be used to improve students’ problem-solving skills is theSTEM learning approach. This study aims to determine students’ problem-solvingabilities before and after the implementation of the STEM learning approach and toanalyze the effect of the STEM learning approach on students’ problem-solvingabilities in IPAS learning for fifth grade students at SDN 70 Boddia. This studyemployed an experimental research design using a Quasi-Experimental method.Quasi-Experimental research is a type of research that has a control group butcannot fully control external variables that may influence the implementation of theexperiment. The data collection techniques used were observation anddocumentation. The data were analyzed using descriptive statistical analysistechniques and SPSS 26 statistical analysis The results of the study indicate thatthere is an effect of the STEM learning approach on students’ problem-solvingabilities in IPAS learning for fifth grade students at SDN 70 Boddia. This is shownby the post-test average score of 89.21%. Based on the results of the independentsample t-test hypothesis testing, the Sig. (2-tailed) equal variance assumed valuewas 0.001, which indicates that 0.001 < 0.05. In other words, H0 was rejected andH1 was accepted, meaning that there is a significant effect of the STEM learningapproach on students’ problem-solving abilities in IPAS learning for fifth gradestudents at SDN 70 BoddiaKeywords : STEM Learning Approach, Problem Solving, Quantitative Researc